PJI EDGe 2016 / Division of Research and Industrial Linkages - Universiti Teknologi MARA, Melaka, Division of Research and Industrial Linkages (Division of Research and Industrial Linkages, 2016)
First and foremost, I would like to congratulate the Research and Industry Linkages Division of UiTM Melaka, or better known as PJI, for successfully launching their first annual report, PJI EDGe, this year. This report provides the evidence of all the initiatives taken by all the nine units under PJI in the year 2016. It is indeed wonderful that academicians, researchers and staff from UiTM Melaka have been able to make the time and effort to partake in various projects and activities that contribute towards the production of world class researches, innovations,consultations and publications.What was achieved in 2016 should not stop there. These achievements should serve as the catalyst for us to generate and take on more initiatives that propel UiTM Melaka towards greater excellence. This is a sure way of improving existing methods, materials, and teaching and learning environments; and expanding on falsified or acknowledged concepts. This is the kind of climate that we need if competence and effectiveness are to be accomplished in any given field in institutions of higher learning.Last but not least, I would like to take this opportunity to thank the PJI EDGe committee members who have worked so hard to put this annual report together amidst their busy schedules and responsibilities. I would also like to thank all the writers for sharing their achievements with us